An experimental extreme drought reduces the likelihood of species to coexist despite increasing intransitivity in competitive networks. (16th April 2018) - Matías, Luis; Godoy, Oscar; Gómez‐Aparicio, Lorena; Pérez‐Ramos, Ignacio M.
Abstract: Very little is known about how variation in environmental conditions alters the strength and the structure of competitive networks and what are the consequences of this for species coexistence. We performed a competition experiment with 10 annual plant species to parameterise a population model describing species' dynamics according to their vital rates and pairwise competitive coefficients. Seeds from all species were sown under two different climatic scenarios: (1) right before the first major storm of the growing season and (2) after an imposed fall drought of 2 months simulating an extreme climatic event of intense aridity. Species' demography and competitive responses were used to estimate pairwise stabilising niche differences and average fitness differences. In addition, we used tools from network theory to characterise the structure of multispecies competition from the determinants of species coexistence. Specifically, we evaluated changes in competitive dominance between species pairs, and the prevalence of intransitive competitive relationships for 120 triplets between these two climatic events. The experimental extreme event significantly reduced fitness differences between species pairs. Such an equalising mechanism promotes coexistence. However, niche differences were also reduced in such a way that the number of species pairs whose niche differences overcame their fitness differences was reduced from six to two. Contrary to our expectations, the extreme event did not increase the hierarchy of competitive dominance. Instead, and depending on the technique used, the prevalence of intransitivity remained marginally similar (17% to 22%) or significantly increased from 19.4% to 29.8%. This pattern was likely a consequence of the significant changes in competitive dominance between species pairs (26 changes out of 45; 58%). Although fitness differences were equalised and intransitive competition promoted, our model predicted a lower likelihood of coexistence under the extreme event for both species pairs and triplets, mainly because competitive interactions did not promote enough niche differences to balance the observed fitness asymmetries in our competitive networks. Synthesis . We empirically proved that an extreme climate results in communities with reduced niche and fitness differences in which species are less likely to coexist despite the increasing prevalence of intransitive competition. Abstract : We empirically proved that an extreme climate results in communities with reduced niche and fitness differences in which species are less likely to coexist despite the increasing prevalence of intransitive competition.